2020
DOI: 10.1186/s13033-020-00394-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of common mental disorders among residents of Illu Ababore zone, southwest Ethiopia: a cross-sectional study

Abstract: Background: A common mental disorder is characterized by anxiety, depression, and unexplained somatic symptoms that usually encountered in community and primary care settings. Both short and long term bio psychosocial disabilities are inevitable if common mental disorder is not treated. Despite its impact, the prevalence of common mental disorder in the Illu Ababore zone is not well known. Therefore, this study aimed to assess the prevalence and associated factors of common mental disorder among Ilu Ababore zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
5
10
1
3
Order By: Relevance
“…The nding from the current study showed that estimated prevalence of Common mental disorder was 24.7% it was in line with studies done in Britain at different study settings 24.6% and 24.2% (14,15) and study done Illibabure was reported 27.2% (27) possible reason might be the nature of illness and same instrument used.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The nding from the current study showed that estimated prevalence of Common mental disorder was 24.7% it was in line with studies done in Britain at different study settings 24.6% and 24.2% (14,15) and study done Illibabure was reported 27.2% (27) possible reason might be the nature of illness and same instrument used.…”
Section: Discussionsupporting
confidence: 90%
“…Females were 2.1 time more likely to develop Common mental disorder than males. this ndings supported by different studies like in Ethiopia, Greece, and South Africa( (17,20,23,27)) possible reason could be females are deprived of schooling and receive burden of social and household responsibility than males and also they are highly vulnerable for physical and sexual abuse. In addition to this low socio-economic status of females might have predispose them to higher risk for common mental disorders.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This finding was in line with studies conducted in Britain at different study settings that reported a prevalence estimate of 24.6% and 24.2% respectively [ 14 , 15 ]. It was also in line with another study conducted in Ethiopia’s Illubabore town which reported a prevalence rate of 27.2% [ 27 ]. The possible reasons for the similarity might be attributed to the nature of the instrument (SRQ-20) used in all the studies.…”
Section: Discussionsupporting
confidence: 89%
“…Females were 2.1 times more likely to develop CMDs than males. This finding is also supported by studies conducted in Greece, South Africa and even Ethiopia [ 17 , 20 , 23 , 27 ]. The possible reason might have emanated from biological cause of hormonal difference [ 40 ].…”
Section: Discussionsupporting
confidence: 79%